Perbedaan Pengetahuan dan Sikap Ibu yang Mendapat Penyuluhan Menggunakan Media Aplikasi Android dan yang Mendapat Penyuluhan Menggunakan Booklet tentang Senam Hamil - Tumiur Sormin; Anita Puri (Politeknik Kesehatan Tanjung Karang, 2019)
The pregnancy gymnastics is useful to decrease the difficulties of normal childbirth for mothers, which means the mortalities will be decreased. The pre-survey in Negara RatuVillage, Natar District results in 6 from 10 pregnant women (60%) who don't know what the pregnancy gymnastics use to be, and 100% never do. Lack of knowledge and attitude are the reason pregnant women never do the pregnancy gymnastics. The research goals are knowing the difference between knowledge and attitude of pregnant women who get counseling by android applications and who get from the pregnancy gymnastic booklet in District Natar, South Lampung. This research is a Quasi Experiment type with a pre-test post-test control group design. With 129 population, 2nd and 3rd trimester and 90 samples obtained by probability sampling, divided into 3rd groups, 30th respondents are android application users, 30th respondents used booklet and 30th is controller respondent. Wilcoxon test result: the knowledge of pregnant women before counsel by android average is 10,57, after counsel is 15,67, and p-value=0,000; the attitude of pregnant women before getting counsel average is 46,27 after counsel is 45,03, and p-value=0,56. The knowledge before counsel by booklet average is 12,36, after counsel is 15,33, and p-value=0,000; the attitude before counsel average is 46,50, and after counsel is 48,63, and p-value=0,08. Result test by Mann-Whitney obtained: the difference of average between pregnant women who get knowledge counsel by android application, and of the booklet is 2,13 and p-value=0,68; the difference average attitude is 0,89 and p-value=0,563. The conclusions are no difference between knowledge and attitude the pregnant women who get counsel by android applications and booklets.